Novel Murine Dendritic Cell Lines: A Powerful Auxiliary Tool for Dendritic Cell Research - Fuertes Marraco, Silvia A.; Grosjean, Fréderic; Duval, Anaïs; Rosa, Muriel; Lavanchy, Christine; Ashok, Devika; Haller, Sergio; Otten, Luc; Steiner, Quynh-Giao; Descombes, Patrick; Luber, Christian A.; Meissner, Felix; et al. (Frontiers in Immunology, 2012)
Research in vitro facilitates discovery, screening and pilot experiments, often preceding research in vivo. Several technical difficulties render Dendritic Cell (DC) research particularly challenging, including the low frequency of DC in vivo, thorough isolation requirements, and the vulnerability of DC ex vivo. Critically, there is not as yet a widely accepted human or murine DC line and in vitro systems of DC research are limited. In this study, we report the generation of new murine DC lines, named MutuDC, originating from cultures of splenic CD8α conventional DC (cDC) tumors. By direct comparison to normal WT splenic cDC subsets, we describe the phenotypic and functional features of the MutuDC lines and show that they have retained all the major features of their natural counterpart in vivo, the splenic CD8α cDC. These features include expression of surface markers Clec9A, DEC205, and CD24, positive response to TLR3 and TLR9 but not TLR7 stimuli, secretion of cytokines and chemokines upon activation, as well as cross-presentation capacity. In addition to the close resemblance to normal splenic CD8α cDC, a major advantage is the ease of derivation and maintenance of the MutuDC lines, using standard culture medium and conditions, importantly without adding supplementary growth factors or maturation-inducing stimuli to the medium. Furthermore, genetically modified MutuDC lines have been successfully obtained either by lentiviral transduction or by culture of DC tumors originating from genetically modified mice. In view of the current lack of stable and functional DC lines, these novel murine DC lines have the potential to serve as an important auxiliary tool for DC research.